Personal Financial Management Behavior of Surabaya College Students - Rini Astuti (Journal of Applied Management and Business, 2020)
This study aims to analyze the influence of academic ability, and allowance on the behavior and behavior of college students managing personal finance, with literacy or financial knowledge as intervening. This type of research is causal comparative with quantitative approach. The point of thought used in the research that is being worked on is the Theory of Planed Behavior (TPB). The research method used is discovery or quantitative. The population used is college students who are in Surabaya universities in the 2017-2019 school year. Samples in this study as many as 100 respondents, by means of data collection using questionnaires, the way of determining samples to be applied in this study is stratified random sampling. Analysis helper tools to process the data that will be used this research is SamartPls 3 and hypothesis test.